Analisis Nilai Jual Komoditas Pangan dan Komoditas Peternakan di Kabupaten Langkat - Putri Rahmawati; Abi Waqqosh; Elida Elfi Barus (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the selling value of food commodities and the selling value of livestock commodities in Langkat Regency. And what strategies are used to get high selling value. This research uses qualitative methods and a descriptive approach. This research shows that first, the selling value of food is not yet in line with farmers' current expectations, with fertilizer prices being expensive and limited, but the selling value is still unstable. Meanwhile, the selling value of livestock in the district is still said to be quite stable.